Pengaruh Kepemimpinan, Tuntutan Tugas dan Stres Kerja Terhadap Komitmen Organisasi dan Perilaku Extra Peran Perawat pada Rumah Sakit Umum Cut Meutia Kabupaten Aceh Utara - Iis, EM Yusuf; Aiyub, Aiyub; Sumaryani, Sumaryani (PASAI, 2014)
This study was conducted to determine the influence leadership, task demands and job stress on organizational commitment and effect on organizational citizenship behavior of nurses at the General Hospital Cut Meutia (RSUCM) North Aceh district. The total sample of 154 nurses, and data analysis model used Structural Equation Modeling (SEM). The results of the data analysis found that leadership does not directly affect the organizational commitment but significant positive effect on organizational citizenship behavior. Variable task demands direct significant positive effect on organizational commitment and significant negative effect on organizational citizenship behavior. Meanwhile, work stress variables do not directly affect the organizational commitment and organizational citizenship behavior. Organizational commitment variables significant positif effect on organizational citizenship behavior. Then the variable organizational commitment does not mediate the relationship between leadership and job stress on organizational citizenship behavior, but complete mediation the relationship between the taks demand with organizational citizenship behavior. It is suggested to RSUCM leadership in order to improve organizational commitment and organizational citizenship behavior needs to be improved so that a more open leadership role, providing more confidence and responsibility to nurses with reasonable taks demands and need to maintain the condition of stress nurses at a reasonable and balanced condition.